2009
DOI: 10.1074/jbc.m109.015149
|View full text |Cite
|
Sign up to set email alerts
|

A Pathogenic C Terminus-truncated Polycystin-2 Mutant Enhances Receptor-activated Ca2+ Entry via Association with TRPC3 and TRPC7

Abstract: Mutations in PKD2 gene result in autosomal dominant polycystic kidney disease (ADPKD). PKD2 encodes polycystin-2 (TRPP2), which is a homologue of transient receptor potential (TRP) cation channel proteins. Here we identify a novel PKD2 mutation that generates a C-terminal tail-truncated TRPP2 mutant 697fsX with a frameshift resulting in an aberrant 17-amino acid addition after glutamic acid residue 697 from a family showing mild ADPKD symptoms. When recombinantly expressed in HEK293 cells, wild-type (WT) TRPP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Studies aimed at elucidating the role of the polycystins in this process and how it is altered in ADPKD are summarized in Table 2. 12,3234,39,5065 The results of these studies are not always consistent, likely due to different experimental conditions. For example, reduced IP3-induced calcium release has been observed in experiments where PC1 was either knocked down or overexpressed.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies aimed at elucidating the role of the polycystins in this process and how it is altered in ADPKD are summarized in Table 2. 12,3234,39,5065 The results of these studies are not always consistent, likely due to different experimental conditions. For example, reduced IP3-induced calcium release has been observed in experiments where PC1 was either knocked down or overexpressed.…”
Section: Introductionmentioning
confidence: 84%
“…For example, PC1 interacts with the inositol 1,4,5-trisphosphate receptor (IP3R) and the stromal interaction molecule 1 (STIM1), while PC2 interacts with IP3R, the ryanodine receptor (RyR), TRPV4 and TRPC1, 3, 4 and 7. 3239 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new frameshift mutation, resulting in mild form of ADPKD, has been identified [91]. This mutation leads to the C-terminally truncated TRPP2 channel (E697X) that shows a predominant plasma membrane expression and prominently increased receptor-operated Ca 2+ (ROC) influx in cells expressing TRPC3 or TRPC7.…”
Section: The Trpp Subfamilymentioning
confidence: 99%
“…Recently Li et al (24) demonstrated also that ER-localized PKD1 can interact with the IP 3 R, thereby inhibiting IP 3 -induced Ca 2ϩ release (IICR). Several studies observed an enhancement of intracellular Ca 2ϩ release that was attributed to an effect of TRPP2 (15,23,25,26), but the physiological mechanism of action was not elucidated. On the other hand, Wegierski and co-workers (27) observed that TRPP2 could also act as a passive Ca 2ϩ -leak channel in the ER, thereby lowering the Ca 2ϩ concentration in the ER ([Ca 2ϩ ] ER ), which resulted in an opposite effect and decreased the magnitude of IICR.…”
mentioning
confidence: 99%